Evaluation method for corrosion resistance of oxide film on surface of cold rolled thin plate
By using a weak acid-strong oxidation erosion solution to determine the per-area iron dissolution value of the surface oxide film of the cold-rolled thin sheet, the problem of lack of accurate corrosion resistance evaluation methods in the prior art is solved, and the corrosion resistance of the surface oxide film of the cold-rolled thin sheet is accurately described, and the preparation quality of tin plating products is improved.
Patent Information
- Application Number
- CN202110974523.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-08-24
Smart Images

Figure CN115718078B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for evaluating the performance of a coating on a steel plate surface, and in particular to a method for evaluating the corrosion resistance of an oxide film on the surface of a cold-rolled thin plate. Background Art
[0002] Metal packaging materials represented by tin / chrome-plated products are currently commonly used metal packaging materials. In production, not only the alloy composition must be controlled, but also the cold-rolled thin plates need to go through processes such as hot rolling, cold rolling, annealing, and leveling (or secondary cold rolling). In addition, the cold-rolled thin plates need to be circulated and stored between each process, and then the cold-rolled thin plates are tinned or chrome-plated. Before the cold-rolled thin plates are tinned / chrome-plated, the surface oxide film must be completely cleaned by pickling to ensure the quality of the tin / chrome-plated layer. Therefore, the state of the surface oxide film of the cold-rolled thin plates has an important influence on the preparation of the subsequent tin / chrome-plated layer.
[0003] Generally speaking, the oxide film on the surface of cold-rolled thin plates includes two aspects: one is the oxide film formed during production in the steel plate manufacturing plant, and the other is the growth of the oxide film during transportation and storage after processing and forming. Although the oxide film tends to thicken as the storage time increases, the thickness of the oxide film formed on the surface of the cold-rolled thin plate is still very thin and is usually about 10 nanometers thick. Since the oxide film is not protected by a plating or coating, it is easy to rust under conditions of high temperature and high humidity. In particular, a small amount of easily oxidized elements such as Mn and Si contained in the cold-rolled thin plate form granular oxides on the surface of the cold-rolled thin plate, which form corrosion micro-cells with the iron oxide film, accelerating the speed of rust on the surface of the cold-rolled thin plate, and also greatly restricting the optimization of the pickling process conditions, which has a significant adverse effect on the subsequent coating process.
[0004] If the corrosion resistance of the oxide film on the surface of the cold-rolled sheet is changed through various processes or methods, it will affect the cleaning effect of the pickling of the oxide film on the surface of the cold-rolled sheet. At present, there is no detection method that can accurately characterize or distinguish the corrosion resistance of the 10nm thick oxide film on the surface of the cold-rolled sheet, which to some extent affects the production quality of the subsequent coating process. Summary of the invention
[0005] The purpose of the present invention is to provide a method for evaluating the corrosion resistance of the surface oxide film of a cold-rolled thin plate, which can accurately, quickly and quantitatively describe the corrosion resistance of the surface oxide film of the cold-rolled thin plate, and is used to compare the corrosion resistance differences of the ten-nanometer-thick oxide films on the surfaces of different cold-rolled thin plates.
[0006] The present invention is achieved in that:
[0007] A method for evaluating the corrosion resistance of a surface oxide film of a cold-rolled thin plate comprises the following steps:
[0008] Step 1: prepare NH4SCN solution, C6H5ONa solution, C3H6O3 solution, H2O2 solution, Na2O2 solution and Fe standard solution respectively;
[0009] Step 2: Mix the solutions prepared in step 1 in proportion, and measure the absorbance under ultraviolet light to obtain a Fe standard curve, and obtain a regression curve of the Fe standard curve;
[0010] Step 3: Clean the cold-rolled sheet sample with a weak alkaline solution, take it out and then clean it with an acetone solution;
[0011] Step 4: gas purging the cold rolled sheet sample;
[0012] Step 5: preparing a weak acid-strong oxidizing etching solution, wherein the weak acid-strong oxidizing etching solution includes NH4SCN solution, C6H5ONa solution, C3H6O3 solution, H2O2 solution and Na2O2 solution;
[0013] Step 6: Adjust the pH value of the weak acid-strong oxidizing corrosion solution and place it in a measurement container;
[0014] Step 7: placing the cold-rolled sheet sample in a measuring container, and allowing the weak acid-strong oxidizing etching solution to completely contact the surface of the cold-rolled sheet sample, so that the weak acid-strong oxidizing etching solution corrodes the surface of the cold-rolled sheet sample;
[0015] Step 8: Determine the absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample;
[0016] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2 to calculate the iron content C corresponding to the absorbance, and then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area;
[0017] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample according to the iron dissolution value per unit area of the cold-rolled sheet sample.
[0018] The concentration of the NH4SCN solution is 0.33 mol / L, the concentration of the C6H5ONa solution is 0.33 mol / L, the concentration of the C3H6O3 solution is 0.435 mol / L, the volume concentration of the H2O2 solution is 1%, the concentration of the Na2O2 solution is 0.01 mol / L, and the concentration of the Fe standard solution is 0.1 g / L.
[0019] The step 2 comprises:
[0020] Step 2.1: Take n volumetric flasks, mix the solutions prepared in step 1 in proportion, dilute with water, and shake well to obtain n bottles of mixed solutions with iron content of 0-25 mg / L;
[0021] Step 2.2: Use the mixed solution with 0% Fe content as a blank solution to adjust the absorbance of the reference solution of the UV-visible spectrophotometer to zero, and measure the absorbance of the remaining n-1 bottles of mixed solutions under ultraviolet light;
[0022] Step 2.3: With the horizontal axis representing absorbance and the vertical axis representing iron content, draw the absorbance curve of the n-1 bottle of mixed solution as the Fe standard curve, and obtain the regression curve of the Fe standard curve.
[0023] In the step 2.1, the number n of volumetric flasks is not less than 2; in terms of volume percentage, the mixed solution includes 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution, 0-25% Fe standard solution and the remainder water; in the step 2.2, the wavelength of the ultraviolet light is 470nm.
[0024] In the step 3, the weak alkaline solution is prepared by mixing 1-5 g / L sodium carbonate solution and 1-3 g / L sodium acetate solution; the cleaning time of the cold-rolled thin plate sample in the weak alkaline solution is 5-10 s, and the cleaning time of the cold-rolled thin plate sample in the acetone solution is 3-5 s.
[0025] In the step 5, in the weak acid-strong oxidation etching solution, the concentration of NH4SCN solution is 0.33mol / L, the concentration of C6H5ONa solution is 0.33mol / L, the concentration of C3H6O3 solution is 0.435mol / L, the volume concentration of H2O2 solution is 1%, and the concentration of Na2O2 solution is 0.01mol / L; by volume percentage, the weak acid-strong oxidation etching solution includes 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution and 40% deionized water.
[0026] In step 6, ammonia water or C3H6O3 solution is added to the weak acid-strong oxidizing etching solution to adjust the pH value of the weak acid-strong oxidizing etching solution to 5.5-6.0 and the temperature to 8-12°C.
[0027] In the step 7, the weak acid-strong oxidizing etching solution is in contact with the surface of the cold-rolled sheet sample for 90 seconds; after the surface etching of the cold-rolled sheet sample is completed, the surface of the cold-rolled sheet sample is cleaned with deionized water, and the cleaned solution is added to the weak acid-strong oxidizing etching solution.
[0028] In the step 9, the calculation formula of the iron dissolution value per unit area is: Fe = (C*0.1*V) / S;
[0029] The unit of iron dissolution value per unit area is mg / dm 2 , 0.1 is the unit conversion factor;
[0030] C is the iron content, in mg / L;
[0031] S is the area of the cold rolled sheet sample, in cm 2 ;
[0032] V is the volume of the weak acid-strong oxidizing etching solution.
[0033] In step 10, when the iron dissolution value per unit area is greater than 8 mg / dm 2 When the iron dissolution value per unit area is less than or equal to 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is strong.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention adopts a weak acid-strong oxidizing corrosion solution, which can selectively corrode the surface oxide film of the cold-rolled thin plate, so that the iron in the cold-rolled thin plate is dissolved into the weak acid-strong oxidizing corrosion solution medium. The corrosion resistance of the surface oxide film of the cold-rolled thin plate is evaluated by quickly and accurately calculating the iron content in the solution medium, and the difficulty of cleaning the surface oxide film of the cold-rolled thin steel plate can be effectively predicted, which can provide a theoretical basis for the improvement of the subsequent pickling treatment process of tin-plated products.
[0036] 2. The present invention is based on the iron content dissolved from the cold-rolled thin plate in a weak acid-strong oxidizing corrosion solution medium. It can compare the corrosion resistance differences of the oxide film with a thickness of about ten nanometers on the surface of different cold-rolled thin plates, and can accurately, quickly and quantitatively describe the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate, providing technical support for the protection and inventory turnover of cold-rolled thin steel plates.
[0037] 3. The present invention establishes an evaluation standard for the corrosion resistance of the surface oxide film of different cold-rolled thin plates, which provides an important evaluation index for the control of rust defects and the improvement of pickling process of cold-rolled thin plates, is beneficial to improving the surface quality of surface tin-plated products, reducing the incidence of surface corrosion of tin-plated plates, and improving the qualified rate of tin-plated plate products.
[0038] 4. The present invention establishes an evaluation standard for the corrosion resistance of the surface layers of different cold-rolled thin plates, providing an important evaluation index for the control of substrate corrosion defects and the improvement of pickling processes.
[0039] The present invention selectively corrodes the surface oxide film of the cold-rolled thin plate by a weak acid-strong oxidizing corrosion solution, dissolves the iron in the cold-rolled thin plate, and accurately evaluates the corrosion resistance of the surface oxide film of the cold-rolled thin plate according to the amount of iron dissolved, and is used to compare the corrosion resistance difference of the ten-nanometer-thick oxide film on the surface of different cold-rolled thin plates, providing technical support for the preparation of high-quality surface coatings of the cold-rolled thin plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a Fe standard curve diagram of the corrosion resistance evaluation method of the surface oxide film of the cold-rolled thin plate of the present invention. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0042] A method for evaluating the corrosion resistance of a surface oxide film of a cold-rolled thin plate comprises the following steps:
[0043] Step 1: Prepare NH4SCN (ammonium thiocyanate) solution, C6H5ONa (sodium phenolate) solution, C3H6O3 (citric acid) solution, H2O2 (hydrogen peroxide) solution, Na2O2 (sodium peroxide) solution and Fe (iron) standard solution respectively.
[0044] Preferably, the concentration of the NH4SCN solution is 0.33 mol / L, and it is used as a complexing agent to complex iron ions. The concentration of the C6H5ONa solution is 0.33 mol / L, and it is used as a buffer to reduce the pH fluctuation of the solution. The concentration of the C3H6O3 solution is 0.435 mol / L, which can be used to adjust the pH value of the solution. The volume concentration of the H2O2 solution is 1%, and the concentration of the Na2O2 solution is 0.01 mol / L. The H2O2 solution and the Na2O2 solution are combined oxidants, which can oxidize the divalent iron ions eroded into the solution, and also maintain the density of the oxide film on the surface of the cold-rolled sheet. The concentration of the Fe standard solution is 0.1 g / L.
[0045] Step 2: Mix the solutions prepared in step 1 in proportion, and measure the absorbance under ultraviolet light to obtain a Fe standard curve and a regression curve of the Fe standard curve.
[0046] Step 2.1: Take n volumetric flasks, mix the solutions prepared in step 1 in proportion, dilute with water, and shake well to obtain n bottles of mixed solutions with iron content of 0-25 mg / L.
[0047] Preferably, the number n of volumetric flasks is not less than 2, and the number of volumetric flasks can be adjusted according to actual test requirements. The more volumetric flasks there are, the higher the accuracy of the obtained Fe standard curve.
[0048] In terms of volume percentage, the mixed solution includes 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution, 0-25% Fe standard solution and the balance water.
[0049] Preferably, 7 volumetric flasks are taken and marked as No. 1 to No. 7 in sequence, the volume of each volumetric flask is 100 ml, and the proportion of the mixed solution is shown in Table 1.
[0050] Table 1 Ratios of 7 mixed solutions
[0051]
[0052] Step 2.2: Use the mixed solution with 0% Fe content as a blank solution to adjust the absorbance of the reference solution of the UV-visible spectrophotometer to zero, and measure the absorbance of the remaining n-1 bottles of mixed solution by the UV-visible spectrophotometer. Since the same sample will obtain different data relative to different reference solutions, adjusting the absorbance of the reference solution to zero can reduce the data measurement error.
[0053] The absorbance zeroing method of the UV-visible spectrophotometer is: first adjust the UV-visible spectrophotometer to the transmittance function, and adjust the transmittance of the black cuvette to 0. Then adjust the UV-visible spectrophotometer to the absorbance function, and adjust the reference solution cuvette to 0. If the UV-visible spectrophotometer used has a one-key zeroing function, the absorbance of the reference solution can also be zeroed with one key, and then the test can be carried out. The absorbance zeroing method of the UV-visible spectrophotometer can be adjusted according to the functions of different equipment, and will not be repeated here.
[0054] After comparing the ultraviolet measurement data of different wavelengths, the ultraviolet light with a wavelength of 470nm is the maximum absorption wavelength of the absorbance of the absorption spectrum of the mixed solution system. Preferably, the wavelength of the ultraviolet light is 470nm. When the wavelength is 470nm, the influence of all ions in the mixed solution except the ion to be measured can be completely eliminated, thereby minimizing the experimental error.
[0055] Step 2.3: With the horizontal axis representing absorbance and the vertical axis representing iron content (mg / L), draw the absorbance curve of the n-1 bottle of mixed solution as the Fe standard curve, and obtain the regression curve of the Fe standard curve through regression calculation. Figure 1 The broken line in the figure is the Fe standard curve, the straight line is the regression curve of the Fe standard curve, and the equation of the regression curve is y=13.953x-2.0394, which is used for the conversion of absorbance-iron content.
[0056] Step 3: Clean the cold-rolled sheet sample with a weak alkaline solution to remove the oily substance on the surface of the cold-rolled sheet sample, and then clean it with an acetone solution to further remove the oily substance on the surface of the cold-rolled sheet sample and remove the residual weak alkaline solution.
[0057] Preferably, the weak alkaline solution is prepared by mixing 1-5 g / L sodium carbonate solution and 1-3 g / L sodium acetate solution.
[0058] Preferably, the cleaning time of the cold-rolled thin plate sample in the weak alkaline solution is 5-10 seconds, and the cleaning time of the cold-rolled thin plate sample in the acetone solution is 3-5 seconds.
[0059] Preferably, the cold-rolled sheet sample has an area of 21 cm 2 The circular plate structure of the cold-rolled thin plate specimen can be adjusted according to actual experimental requirements.
[0060] Step 4: Gas purges the cold-rolled sheet sample to prevent further oxidation of the surface oxide film of the cold-rolled sheet sample, thus ensuring the accuracy of the test process.
[0061] Preferably, the gas used to purge the cold-rolled sheet sample is nitrogen, and the purge time is 15-30s. The purge gas can be adjusted according to actual test needs.
[0062] Step 5: Prepare a weak acid-strong oxidizing corrosion solution, which includes NH4SCN solution, C6H5ONa solution, C3H6O3 solution, H2O2 solution, Na2O2 solution and deionized water. The weak acid of the weak acid-strong oxidizing corrosion solution is reflected in the coupling effect of C6H5Ona solution and C3H6O3 solution, and it acts as a buffer, which can strictly control the pH fluctuation of the weak acid-strong oxidizing corrosion solution. The strong oxidation of the weak acid-strong oxidizing corrosion solution is reflected in the coupling effect of the two oxidants, H2O2 solution and Na2O2 solution, which can avoid oxidation and reduce oxidation efficiency. The weak acid-strong oxidizing corrosion solution can corrode the cold-rolled thin plate sample matrix through the pores of the oxide film through the H2O2 solution and the Na2O2 solution, dissolve the iron on the matrix without corroding the oxide film itself, and its chemical reaction is as follows:
[0063] Fe+2H + =Fe 2+ +H2↑
[0064] 2Fe 2+ +2H2O2=2Fe 3+ +2H2O+O2↑
[0065] Fe 3+ +3SCN - =Fe(SCN)3.
[0066] Preferably, in the weak acid-strong oxidizing corrosion solution, the concentration of NH4SCN solution is 0.33mol / L, the concentration of C6H5ONa solution is 0.33mol / L, the concentration of C3H6O3 solution is 0.435mol / L, the volume concentration of H2O2 solution is 1%, and the concentration of Na2O2 solution is 0.01mol / L; by volume percentage, the weak acid-strong oxidizing corrosion solution comprises 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution and 40% deionized water, and the total volume is preferably 100ml.
[0067] Step 6: Adjust the pH of the weak acid-strong oxidizing etching solution to 5.5-6.0 and place it in the measurement container.
[0068] Preferably, ammonia water or C3H6O3 solution is added to the weak acid-strong oxidizing etching solution to adjust the pH value of the weak acid-strong oxidizing etching solution to 5.5-6.0 and the temperature to 8-12°C.
[0069] Step 7: Place the cold-rolled sheet sample in a measuring container, and allow the weak acid-strong oxidation etching solution to completely contact the surface of the cold-rolled sheet sample, so that the weak acid-strong oxidation etching solution can erode the surface of the cold-rolled sheet sample; after the surface etching of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with deionized water, and add the washed solution to the weak acid-strong oxidation etching solution to ensure that all dissolved iron ions can enter the weak acid-strong oxidation etching solution without remaining on the surface of the cold-rolled sheet sample, thereby ensuring the detection accuracy of the absorbance. The volume of deionized water can be adjusted according to the actual experimental situation, for example, 20 ml.
[0070] Due to the porosity of the oxide film, the iron in the cold-rolled thin plate sample will dissolve into the solution medium through the fragile parts of the surface oxide film through the tiny pores. The dissolved iron is oxidized into trivalent iron ions, which react with ammonium thiocyanate to generate red ferric thiocyanate and develop color. The dissolved iron content is measured by the colorimetric method to indicate the porosity of the oxide film, and then characterize the corrosion resistance of the surface oxide film of the cold-rolled thin plate sample.
[0071] Preferably, the weak acid-strong oxidizing etching solution is in contact with the surface of the cold-rolled sheet sample for 90 seconds, at which time the absorbance difference between different weak acid-strong oxidizing etching solutions is most obvious, the absorbance range is moderate, and it is easier to measure and compare.
[0072] Step 8: Use a UV-visible spectrophotometer to measure the absorbance of the weak acid-strong oxidizing etch solution after etching the cold-rolled sheet sample. Before the measurement, a blank solution or the one-key zeroing function of the device can be used to zero the absorbance. The zeroing method is the same as the zeroing method in step 2.2 and will not be repeated here.
[0073] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2 to calculate the iron content C corresponding to the absorbance, and then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, and the calculation formula is:
[0074] Fe=(C*0.1*V) / S Formula (1)
[0075] Wherein, C is the iron content in mg / L.
[0076] S is the area of the cold rolled sheet sample.
[0077] V is the volume of the weak acid-strong oxidizing etching solution.
[0078] 0.1 is the unit conversion factor.
[0079] The iron content of different cold-rolled thin plate samples, i.e., the iron dissolution value per unit area, is determined by formula (1) and is used to characterize the porosity of the oxide film on the surface of the cold-rolled thin plate samples.
[0080] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample according to the iron dissolution value per unit area of the cold-rolled sheet sample.
[0081] When the iron dissolution value per unit area is greater than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is weak.
[0082] When the iron dissolution value per unit area is less than or equal to 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is strong.
[0083] Embodiment 1:
[0084] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0085] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0086] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0087] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0088] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0089] Step 3: The cold rolled sheet sample is 21cm in area 2 The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 6 seconds, and then taken out and cleaned with 100 ml acetone solution for 4 seconds.
[0090] Step 4: Purge the cold-rolled sheet sample with nitrogen for 20 seconds.
[0091] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0092] Step 6: Adjust the pH value of the weak acid-strong oxidizing etching solution to 5.5 with aqueous ammonia at 10°C and place it in a measurement container.
[0093] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2 Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0094] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.364.
[0095] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=16.992. Then calculate the iron content (mg / dm 2) is the iron dissolution value per unit area, Fe = (16.992*0.1*120) / 21 = 9.710 mg / dm 2 .
[0096] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: the iron dissolution value per unit area is greater than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is weak.
[0097] Embodiment 2:
[0098] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0099] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0100] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0101] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0102] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0103] Step 3: The cold rolled sheet sample is 21cm in area 2 The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 7 seconds, and then taken out and cleaned with 100 ml acetone solution for 5 seconds.
[0104] Step 4: Purge the cold-rolled sheet sample with nitrogen for 23 seconds.
[0105] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0106] Step 6: Adjust the pH of the weak acid-strong oxidizing etching solution to 5.7 with aqueous ammonia at 9°C and place it in a measurement container.
[0107] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2 Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0108] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.412.
[0109] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=17.662. Then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, Fe = (17.662*0.1*120) / 21 = 10.093 mg / dm 2 .
[0110] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: the iron dissolution value per unit area is greater than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is weak.
[0111] Embodiment 3:
[0112] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0113] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0114] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0115] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0116] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0117] Step 3: The cold rolled sheet sample is 21cm in area 2 The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 8 s, and then taken out and cleaned with 100 ml acetone solution for 5 s.
[0118] Step 4: Purge the cold-rolled sheet sample with nitrogen for 17 seconds.
[0119] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0120] Step 6: Adjust the pH of the weak acid-strong oxidizing etching solution to 6.0 with aqueous ammonia at 11°C and place it in a measurement container.
[0121] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2 Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0122] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.092.
[0123] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=13.197. Then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, Fe = (13.197*0.1*120) / 21 = 7.541 mg / dm 2 .
[0124] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: The iron dissolution value per unit area is less than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is strong.
[0125] Embodiment 4:
[0126] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0127] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0128] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0129] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0130] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0131] Step 3: The cold rolled sheet sample is 21cm in area 2The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 8 s, and then taken out and cleaned with 100 ml acetone solution for 4 s.
[0132] Step 4: Purge the cold-rolled sheet sample with nitrogen for 25 seconds.
[0133] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0134] Step 6: Adjust the pH value of the weak acid-strong oxidizing etching solution to 5.8 with aqueous ammonia at 10°C and place it in a measurement container.
[0135] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2 Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0136] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.492.
[0137] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=18.778. Then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, Fe = (18.778*0.1*120) / 21 = 10.730 mg / dm 2 .
[0138] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: the iron dissolution value per unit area is greater than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is weak.
[0139] Embodiment 5:
[0140] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0141] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0142] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0143] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0144] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0145] Step 3: The cold rolled sheet sample is 21cm in area 2 The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 6 seconds, and then taken out and cleaned with 100 ml acetone solution for 3 seconds.
[0146] Step 4: Purge the cold-rolled sheet sample with nitrogen for 22 seconds.
[0147] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0148] Step 6: Adjust the pH value of the weak acid-strong oxidizing etching solution to 5.7 with aqueous ammonia at 9°C and place it in a measurement container.
[0149] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0150] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.005.
[0151] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=11.983. Then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, Fe = (11.983*0.1*120) / 21 = 6.848 mg / dm 2 .
[0152] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: The iron dissolution value per unit area is less than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is strong.
[0153] Embodiment 6:
[0154] Step 1: Prepare 0.33 mol / L NH4SCN solution, 0.33 mol / L C6H5ONa solution, 0.435 mol / L C3H6O3 solution, 1% H2O2 solution, 0.01 mol / L Na2O2 solution and 0.1 g / L Fe standard solution respectively.
[0155] Step 2: Mix the solutions prepared in step 1 according to the proportions, and measure the absorbance under ultraviolet light to obtain a Fe standard curve.
[0156] Step 2.1: Take 7 100ml volumetric flasks, mark them as No1-No7, mix the solutions prepared in step 1 in proportion, dilute them to 100ml with water, and shake them well to obtain 7 bottles of mixed solutions with Fe content of 0-25mg / L, as shown in Table 1.
[0157] Step 2.2: The mixed solution with 0% Fe content was used as a blank solution for adjusting the absorbance to zero, and the absorbance of the remaining 6 bottles of mixed solutions was measured by an ultraviolet visible spectrophotometer at a wavelength of 470 nm.
[0158] Step 2.3: With the horizontal axis being absorbance and the vertical axis being iron content (mg / L), draw an absorbance curve as the Fe standard curve and its regression curve. The regression curve formula is y=13.953x-2.0394, as shown in the attached figure. Figure 1 shown.
[0159] Step 3: The cold rolled sheet sample is 21cm in area 2 The round cold-rolled thin steel plate was cleaned with 100 ml weak alkaline solution mixed with 2 g / L sodium carbonate solution and 1 g / L sodium acetate solution for 6 seconds, and then taken out and cleaned with 100 ml acetone solution for 4 seconds.
[0160] Step 4: Purge the cold-rolled sheet sample with nitrogen for 19 seconds.
[0161] Step 5: By volume percentage, prepare 100 ml of weak acid-strong oxidizing etching solution with 10% 0.33 mol / L NH4SCN solution, 10% 0.33 mol / L C6H5ONa solution, 20% 0.435 mol / L C3H6O3 solution, 10% 1% H2O2 solution, 10% 0.01 mol / L Na2O2 solution and 40% deionized water.
[0162] Step 6: Adjust the pH value of the weak acid-strong oxidizing etching solution to 5.6 with aqueous ammonia at 11°C and place it in a measurement container.
[0163] Step 7: Place the cold rolled sheet sample in a cup with an area of 21 cm 2 Put the container lid in a circular measuring container, put it on, turn the measuring container upside down, and let the weak acid-strong oxidizing etch solution completely contact the surface of the cold-rolled sheet sample for 90 seconds, so that the weak acid-strong oxidizing etch solution can erode the surface of the cold-rolled sheet sample. After the surface erosion of the cold-rolled sheet sample is completed, wash the surface of the cold-rolled sheet sample with 20 ml of deionized water, and add the washed solution to the weak acid-strong oxidizing etch solution.
[0164] Step 8: The absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample under ultraviolet light with a wavelength of 470 nm was measured to be 1.426.
[0165] Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2, and calculate the iron content corresponding to the absorbance C=17.858. Then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area, Fe = (17.858*0.1*120) / 21 = 10.205 mg / dm 2 .
[0166] Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample based on the iron dissolution value per unit area of the cold-rolled sheet sample: the iron dissolution value per unit area is greater than 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is weak.
[0167] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for evaluating the corrosion resistance of a surface oxide film of a cold-rolled sheet, characterized in that: The following steps are involved: Step 1: prepare NH4SCN solution, C6H5ONa solution, C3H6O3 solution, H2O2 solution, Na2O2 solution and Fe standard solution respectively; Step 2: Mix the solutions prepared in step 1 in proportion, and measure the absorbance under ultraviolet light to obtain a Fe standard curve, and obtain a regression curve of the Fe standard curve; Step 3: Clean the cold-rolled sheet sample with a weak alkaline solution, take it out and then clean it with an acetone solution; Step 4: gas purging the cold rolled sheet sample; Step 5: preparing a weak acid-strong oxidizing etching solution, wherein the weak acid-strong oxidizing etching solution includes NH4SCN solution, C6H5ONa solution, C3H6O3 solution, H2O2 solution and Na2O2 solution; In the weak acid-strong oxidation etching solution, the concentration of NH4SCN solution is 0.33mol / L, the concentration of C6H5ONa solution is 0.33mol / L, the concentration of C3H6O3 solution is 0.435mol / L, the volume concentration of H2O2 solution is 1%, and the concentration of Na2O2 solution is 0.01mol / L; in terms of volume percentage, the weak acid-strong oxidation etching solution includes 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution and 40% deionized water; Step 6: Adjust the pH value of the weak acid-strong oxidizing erosion solution to 5.5-6.0 and place it in a measurement container; Step 7: placing the cold-rolled sheet sample in a measuring container, and allowing the weak acid-strong oxidizing etching solution to completely contact the surface of the cold-rolled sheet sample, so that the weak acid-strong oxidizing etching solution corrodes the surface of the cold-rolled sheet sample; Step 8: Determine the absorbance of the weak acid-strong oxidizing etching solution after etching the cold-rolled sheet sample; Step 9: Substitute the absorbance obtained in step 8 into the regression curve equation of the Fe standard curve obtained in step 2 to calculate the iron content C corresponding to the absorbance, and then calculate the iron content (mg / dm 2 ) is the iron dissolution value per unit area; Step 10: Evaluate the porosity of the oxide film on the surface of the cold-rolled sheet sample according to the iron dissolution value per unit area of the cold-rolled sheet sample.
2. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: The concentration of the NH4SCN solution is 0.33 mol / L, the concentration of the C6H5ONa solution is 0.33 mol / L, the concentration of the C3H6O3 solution is 0.435 mol / L, the volume concentration of the H2O2 solution is 1%, the concentration of the Na2O2 solution is 0.01 mol / L, and the concentration of the Fe standard solution is 0.1 g / L.
3. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: The step 2 comprises: Step 2.1: Take n volumetric flasks, mix the solutions prepared in step 1 in proportion, dilute with water, and shake well to obtain n bottles of mixed solutions with iron content of 0-25 mg / L; Step 2.2: Use the mixed solution with 0% Fe content as a blank solution to adjust the absorbance of the reference solution of the UV-visible spectrophotometer to zero, and measure the absorbance of the remaining n-1 bottles of mixed solutions under ultraviolet light; Step 2.3: With the horizontal axis representing absorbance and the vertical axis representing iron content, draw the absorbance curve of the n-1 bottle of mixed solution as the Fe standard curve, and obtain the regression curve of the Fe standard curve.
4. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 3, characterized in that: In the step 2.1, the number n of volumetric flasks is not less than 2; in terms of volume percentage, the mixed solution includes 10% NH4SCN solution, 10% C6H5ONa solution, 20% C3H6O3 solution, 10% H2O2 solution, 10% Na2O2 solution, 0-25% Fe standard solution and the remainder water; in the step 2.2, the wavelength of the ultraviolet light is 470nm.
5. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: In the step 3, the weak alkaline solution is prepared by mixing 1-5 g / L sodium carbonate solution and 1-3 g / L sodium acetate solution; the cleaning time of the cold-rolled thin plate sample in the weak alkaline solution is 5-10 s, and the cleaning time of the cold-rolled thin plate sample in the acetone solution is 3-5 s.
6. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: In step 6, ammonia water or C3H6O3 solution is added to the weak acid-strong oxidizing etching solution to adjust the pH value of the weak acid-strong oxidizing etching solution to 5.5-6.0 and the temperature to 8-12°C.
7. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: In the step 7, the weak acid-strong oxidizing etching solution is in contact with the surface of the cold-rolled sheet sample for 90 seconds; after the surface etching of the cold-rolled sheet sample is completed, the surface of the cold-rolled sheet sample is cleaned with deionized water, and the cleaned solution is added to the weak acid-strong oxidizing etching solution.
8. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: In the step 9, the calculation formula of the iron dissolution value per unit area is: Fe = (C*0.1*V) / S; The unit of iron dissolution value per unit area is mg / dm 2 , 0.1 is the unit conversion factor; C is the iron content, in mg / L; S is the area of the cold rolled sheet sample, in cm 2 ; V is the volume of the weak acid-strong oxidizing etching solution.
9. The method for evaluating the corrosion resistance of the surface oxide film of the cold-rolled sheet according to claim 1, characterized in that: In step 10, when the iron dissolution value per unit area is greater than 8 mg / dm 2 When the iron dissolution value per unit area is less than or equal to 8 mg / dm 2 When the temperature is high, the corrosion resistance of the oxide film on the surface of the cold-rolled thin plate sample is strong.
Citation Information
Patent Citations
Method for evaluating corrosion resistance of surface of chrome-plated plate
CN110132825A